2021
DOI: 10.1039/d1dt02787e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity towards oxygen electrocatalysis for rechargeable Zn–air batteries by alloying Fe and Co in N-doped carbon

Abstract: Large-scale application of rechargeable Zn-air batteries requires low-cost electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) as alternatives to noble metals. Herein, FeCo nanoparticles embedded in N-doped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…49-1568) corresponded with CoFe catalyst. 45 These XRD results suggest that the phases of each metal compounds and alloy are well formed. Additionally, low-intensity peaks in Co 2 N/Fe 3 N and CoFe catalysts at lower angles are caused by potassium CN compounds derived from PBA precursor in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…49-1568) corresponded with CoFe catalyst. 45 These XRD results suggest that the phases of each metal compounds and alloy are well formed. Additionally, low-intensity peaks in Co 2 N/Fe 3 N and CoFe catalysts at lower angles are caused by potassium CN compounds derived from PBA precursor in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…4, the I D / I G of MoO 2 /Mo 2 C/C was 1.75, which was higher than the I D / I G (1.39) of the MoO 2 /Mo 2 C and the I D / I G (1.06) of Vulcan XC-72R, which indicated that the composition of the transition metal compound MoO 2 /Mo 2 C did improve the ORR electron transfer ability of the MoO 2 /Mo 2 C/C. 29,30…”
Section: Resultsmentioning
confidence: 93%
“…[20][21][22] Therefore, there is urgency to develop low-cost, durable, and active multifunctional catalyst materials that can catalyse simultaneously both the ORR and OER. Some of the most promising candidates for substituting expensive noble metal-based catalysts are carbonbased materials that are co-doped with nitrogen and transition metal(s), like Fe and Co. [23][24][25][26] Furthermore, carbon-based materials are excellent catalyst supports, due to their low cost, good electrical conductivity, durable structure, resistance to acids and bases, and good adjustability. 16,20,[26][27][28] However, the synthesis of a multifunctional catalyst material, which catalyses both reactions simultaneously, can be a great challenge due to the need for different catalytic sites and mechanisms.…”
Section: Introductionmentioning
confidence: 99%